Echocardiography of the right ventricle in athlete's heart and hearts of normal size compared to magnetic resonance imaging: Which measurements should be applied in athletes? - Scharhag, J.; Thünenkötter, T.; Urhausen, A.; Schneider, G.; Kindermann, W. (International Journal of Sports Medicine, 2010)
Right ventricular (RV) pathologic hypertrophy and cardiomyopathy have been reported to be related to ventricular arrhythmias and sudden cardiac death in athletes. However, it is unclear which echocardiographic measurements reflect RV dimensions in athlete's heart (AH) correctly. We aimed to compare two-dimensional echocardiography of the RV in AH and normal hearts to magnetic resonance imaging (MRI), and derive recommendations for RV echocardiography in athletes. Twenty-three healthy male endurance athletes with AH (A; 28±4 yrs) and 26 healthy untrained males (C; 26±4 yrs) matched for body-dimensions were examined. In recommended echocardiographic parasternal and 4-chamber views, three enddiastolic RV free wall-thicknesses (T1,T5,T9) and RV diameters were determined (M-mode enddiastolic diameter [RV-EDD]; longitudinal [RV-LAX], sagittal, outflow-tract and tricuspid valve anulus diameters). MRI determined RV enddiastolic volumes (RV-EDV) and masses (RVM) in A and C were: 162±29 vs. 136±15 ml and 76±10 vs. 59±13 g (p<0.001). Significant correlations between RV-EDV and RV-EDD (r=0.49; p=0.001) as well as RV-LAX (r=0.38; p=0.01), and RVM and T5 (r=0.52; p=0.01) were found. For RV echocardiography, significant differences between A and C were documented for RV-EDD (medians [quartiles]: A: 26 mm [24/29 mm]; C: 22 mm [21/27 mm]; p=0.04; measurable in 49/49 subjects), and in the parasternal short axis view for T5 (A: 6.0 mm [5.4/7.8 mm]; C: 5.0 mm [4.5/5.2 mm]; p=0.04; measurable in 22/49). In conclusion, two-dimensional echocardiographic RV measurements offer only a limited potential to reflect true RV dimensions. Only RV-EDD may differentiate between normal hearts and exercise related RV adaptations in AH, and is the only recommendable parameter to be measured in athletes routinely. In unclear cases additional methods should be used to examine the RV in athletes.